ROLE OF INTRA-UTERINE INSEMINATION AND SPERM PREPARATION TECHNIQUES IN TREATMENT OF UNEXPLAINED INFERTILITY AND MALE INFERTILITY - KUMAR, SUSHIL (Med J Armed Forces India, 2000)
Role of intrauterine insemination (IUI) in infertile couples is evaluated. Patients selected for the study belonged to two categories-Unexplained infertility(34 patients) and Male infertility (30 patients). In all the patients selected for IUI ovarian hyperstimulation was carried out with clomiphene citrate. Two techniques of sperm preparation were used – swim-up technique and mono-percoll gradient separation technique. Pregnancy rates of 15.6% per patient and 7% per cycle respectively were achieved which are comparable with other studies. Mono-percoll sperm separation technique was found more effective in treatment of Male infertility (oligo-asthenospermic semen sample).